Suppressing power output fluctuations of photovoltaic power plants. (15th November 2017) - Anvari, M.; Werther, B.; Lohmann, G.; Wächter, M.; Peinke, J.; Beck, H.-P.
Highlights: Intermittent PV power is modelled by a stochastic dynamical jump-diffusion equation. The response of a laboratory set up is assessed for different PV power jump rates. A battery-and-inverter-based technique suppresses the PV-induced fluctuations. Abstract: The use of solar photovoltaic (PV) power has recently increased in electric distribution grids. However, the stochastic properties of solar energy, such as intermittency (i.e. the presence of a correlated high frequency of large fluctuations), can negatively affect power quality and cause grid instabilities, especially in microgrids. In this study, we differentiate the diffusive and jumpy characteristics of solar power and introduce a stochastic dynamical jump-diffusion equation to model non-gaussian PV power. Using the obtained dynamical equation, we generate new synthetic data sets with varying jump rates. Finally, we implement a straightforward filtering method, i.e. a combination of an inverter and a battery storage system to show the applicability of our proposed stochastic method.